Towards an Epistemology of the South. Decoloniality of informative knowledge-power and the new Latin American Communicology. A critical reading on mediation from indigenous cultures - Herrera Huérfano, Eliana (2016)
In this article we propound an Epistemology of the South for the Latin American Communicology, as re-articulation of the social mediation critical theory, based on the emancipatory and antagonist academic culture of the Latin American School of Communication (ELACOM) as new Political Economy of Knowledge at the service of imagination and creativity of indigenous peoples. From Freire to Escobar, from Martin-Barbero and Garcia Canclini to Dussel and Quijano, and postcolonial studies, through Boaventura de Sousa Santos, the commitment for decoloniality of informative knowledge-power poses challenge to reformulate the basis of communicational scientific discourse from a criticism of the mediating power of Anglo-American hegemonic thinking from Native American cultural paradigm.